Students’ Perception on The Effectiveness of Blackboard As A Learning Platform In SEGi University - Azizan, Nur Syamimi bt Mohamad; Bakher, Azni bt Mohd; Sundram, Pauline Hebert; Yee, Song Jia (International Journal of Psychosocial Rehabilitation, 2020)
Online learning platforms have become a prominent tool in higher education institutions in order to enhance teaching and learning environment. Blackboard is a type of learning management system (LMS) used in many tertiary institutions. Systematic Education Group International (SEGi) has been using Blackboard Learn since August 2015 in order to provide better accessibility for course content and coursework assessment. This article aims to gauge the students’ perception on the appropriateness of Blackboard Learn as a learning tool and to identify which features in Blackboard Learn are perceived as most useful by the students. Students’ perceptions were assessed by using quantitative method. The questionnaires were adopted from Heirdsfield, A., Walker, S., Tambyah, M., & Beutel, D. (2011) and distributed randomly to SEGi’s students for data collection. The findings show that majority of the students perceived Blackboard as a favourable platform for their learning. The features that the students found most useful is downloading lecture content or lesson materials and lecture power point presentations. However, the results also reflect that certain features have not been fully utilised in the present. More features can be explored in the future to provide better learning experience for the students.